PENERAPAN DISIPLIN TERHADAP APARATUR SIPIL NEGARA DI LINGKUNGAN SEKRETARIAT DAERAH KABUPATEN PIDIE - Hamdiyah Hamdiyah (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2018)
Civilian apparatus of state that have integrity, professional, neutral andfree from political intervention, clean from corruption practice, collusion andnepotism, and able to organize public service for society, among others, can berealized if ASN have high discipline in the implementation of the main task andits function -day. Therefore, the Government has set the legal basis fordisciplinary enforcement for the ASN through Government Regulation Number53 of 2010 on Civil Service Discipline. However, in practice within the RegionalSecretariat of Pidie District, there are ASNs who have been sentenced todisciplinary discipline either mild, moderate or severe disciplinary punishment inaccordance with the severity of the offense. However, on the other side it turns outthat the leadership of the Regional Secretariat of Pidie Regency is too careful inapplying punishment against ASN that violates the discipline, besides giving lessreward to the disciplined ASN in performing daily tasks. This research is adevelopment in the field of science and technology in the realm of legal sciencebecause research aims to reveal the truth or at least approach the truth that is madesystematically, methodologically and logically. Therefore, in the writing of thisthesis, juridical normative and empirical sociological research is used. Wherenormative juridical research is research conducted by researching library materialsor better known as secondary data such as books, legislation or other readingmaterial related to the discussion. While empirical sociological research isresearch conducted by researching into the field by conducting interviews orbetter known as primary data. In the Regional Secretariat of Pidie District, theapplication of discipline to ASN is done by apple every Monday morning, attendance by using fingerprint attendance machine (finger print), suddeninspection (sidak) to room section in certain time, and disciplinary punishment.The application of the discipline has not been optimal yet, as the rightful officer istoo careful to impose disciplinary punishment. The obstacles faced by theRegional Secretariat of Pidie Regency in the application of the discipline to ASNin its ranks include many ASNs that take the banking credit, the RegionalSecretariat has not been able to improve the welfare of ASN, the weak supervisionof the direct superior, the occurrence of exemplary crisis among ASN itself, andthe work pattern ASN that is not in accordance with the spirit of transparency. Thelegal arrangement on ASN discipline is sufficiently clear to be regulated in theapplicable legislation, but in its implementation it is not necessarily able to runwell because there are obstacles faced by authorized officials in handling theproblem of ASN discipline. It is suggested to the leadership officers in the ranksof Pidie District Secretariat to pay attention to the ability of loan repayment by ASN when applying for credit and must be known by the leader, many ASN canno longer keep the work discipline because its monthly income is tied to bankcredit which is relatively easy to be taken by ASN from a government bank. Thepolicy of the leaders of the Pidie District Secretariat who decided to underscorethe less disciplined ASN after receiving several warnings should be continued forthe next period. It requires firmness or consistency in disciplinary enforcementagainst anyone who violates the discipline of ASN by disciplining punishment(punishment) in accordance with the level of error. On the other hand, there mustalso be reward to ASN achievers.